Characterization and Cytotoxic Activity of Cytosine Deaminase Enzyme Purified from Locally Isolated Escherichia coli (Baghdad Science Journal, 2018)
This research was aimed to the purification and characterization of cytosine deaminase as a medically important enzyme from locally isolated Escherichia coli; then studying its cytotoxic anticancer effects against colon cancer cell line. Cytosine deaminase was subjected to three purification steps including precipitation with 90% ammonium sulfate saturation, ion exchange chromatography on DEAE-cellulose column, and gel filtration chromatography throughout Sephadex G-200 column. Specific activity of the purified enzyme was increased up to 9 U/mg with 12.85 folds of purification and 30.85% enzyme recovery. Characterization study of purified enzyme revealed that the molecular weight of cytosine deaminase produced by E. coli was about 48 KDa, the highest enzyme activity at pH 8.5, and is most stable at pH 7.5 - 9, the enzyme also showed a full activity at a range of temperatures between 45-60 0C. Enzyme activity was strongly inhibited in the presence of mercuric chloride and copper sulphate, when added individually at a constant concentration. However, calcium chloride, manganese chloride and ferric chloride caused a little increase in enzyme activity while sodium azide had no effect on enzyme activity. Upon cytotoxic effect study through micro-cultured tetrazolium assay (MTT) against Caco-2 cell line. Purified cytosine deaminase was found to inhibit the growth of Caco-2 cancer cell line with an IC50 of 242.5 ?g/ml in a comparison to an IC50 of 1864 ?g/ml for crude enzyme. Besides, the enzyme didn’t show significant effect on WRL normal cell line.